Reward Systems and Work Culture in Sugar Factory: A Qualitative Study at Krebet Baru Sugar Factory - Epritamala Pradika Putri; Abdul Hakim; Mohammad Nuh (Lembaga Bale Literasi, 2026)
The sugar factory industry requires an effective reward system to sustain a productive organizational culture. The Krebet Baru Sugar Factory has implemented both financial and non-financial reward mechanisms as part of efforts to build a measurable and productive work culture. This study employs a qualitative descriptive approach, drawing on in-depth interviews with 10 key informants comprising management personnel (Off Farm: 4 persons, On Farm: 2 persons, operational staff: 3 persons, and partner farmers: 1 person) at Krebet Baru Sugar Factory in Malang, East Java, supplemented by field observations and policy document analysis. This research is further contextualized by the results of a thesis study on sugar industry revitalization policy implementation (Permenperin No. 23 of 2016), which provides an empirical basis for understanding how organizational culture and reward systems operate within the broader policy and technological transformation of the sugar factory industry. Data analysis employed thematic analysis techniques. Three main findings emerge: First, reward systems encompassing financial incentives and promotion mechanisms reinforce work discipline and productive performance. Second, employee welfare, particularly through educational instruments and overseas study visits, forms the foundation of a healthy and productive work culture. Third, climate conditions represent the primary contextual challenge in maintaining production targets, requiring organizational flexibility and multi-stakeholder collaboration. These findings align with Grindle’s (2017) policy implementation framework and Rogers’ (1983) diffusion of innovation theory.